Peluang Penggunaan Spermatozoa Epididimis Yang Dikoleksi Setelah Kematian Sebagai Sumber Sel Gamet pada Anjing - I Ketut Puja; IGN Trilaksana; Rudy Lontoh (Universitas Atma Jaya Yogyakarta, 2005)
The purpose of this study was to determine the effect of postmortem time on percentage of life epididymal sperm from postmortem canine caudae epididymides. A total of 9 dog were used and divided into three group. T0 was control group, T1, 3 hours postmortem and T2, 6 hours postmortem. This way, samples were obtained at different times postmortem. Sperm were extracted from the caudae epididymis by means of cuts. The result showed that the percentage of life sperm were 67,16 ± 5.67(T0), 46.33± 5.60 (T1) and 24.00 ± 4.35 respectively. We could appreciate that percentage of life was affected by postmortem time. There was significant decrease life sperm recovered from epididymides postmortem (P<0.01). In conclusion, epididymal sperm from dog undergo decrease of percentage of life, but it could stay acceptable within many hours postmortem. We intepreted these data to indicate that it may still be possible to obtain viable spermatozoa many hours later.